PERAN ADMINISTRASI NEGARA DALAM PRESPEKTIF HUKUM DI INDONESIA - Indah, Oksilia Yulita; Pieris, John; Widiarty, Wiwik S. (jurnal.unprimdn.ac.id, 2024)
This thesis examines the role of state administration from a legal perspective in Indonesia, focusing on its dynamics, challenges, and practical implications. Through a comprehensive review of literature and data collection using methods such as legal document analysis, case studies, interviews, and surveys, this thesis explores the relationship between state administration and law within the framework of a legal state. The analysis highlights the complexity of the state administration's role in carrying out its duties by legal principles, including protecting human rights, enforcing justice, and sustainability of good governance. Furthermore, this thesis identifies the central challenges state administration faces and formulates policy recommendations to enhance its role in ensuring compliance with the law in Indonesia.